Designing learning trajectory to support preservice mathematics teachers' skills in creating and implementing realistic mathematics tasks - Rianasari, Veronika Fitri; Guzon, Angela Fatima H. (Journal on Mathematics Education, 2024)
In mathematics teaching and learning, mathematics tasks embedded in realistic contexts are crucial for developing mathematical concepts, procedures, and the application of mathematical knowledge. Despite this, mathematics teachers often encounter challenges in designing and implementing such realistic mathematics tasks. Therefore, this study aims to construct a learning trajectory to enhance preservice mathematics teachers' abilities to create and implement Realistic Mathematics Tasks (RMTs). Employing a design research methodology, the study comprises three phases: preliminary design, teaching experiment, and retrospective analysis. The data presented in this article are from the first cycle, encompassing all three phases. The research involved four fourth-year preservice mathematics teachers from Sanata Dharma University in Yogyakarta, Indonesia, participating in a preliminary experiment conducted over three months outside their regular coursework. Data were collected through pre-course written tests, observations, interviews, journal reflections, and analyses of the preservice teachers' work. The findings indicate that the learning trajectory effectively raised awareness among preservice teachers about key characteristics of realistic mathematics tasks. This heightened awareness was evident in their reflections and work. Additionally, observations of their teaching practices revealed that preservice teachers valued student reasoning in solving RMTs. However, they faced difficulties in classroom management and guiding students to construct new knowledge actively through their experiences in solving RMTs.